A Critique of Karl Marx’s Political Economy Examined in Light of Nigeria’s Quest for Sustainable Development - Kingsley Patrick Omoruyi; Francis Osadebamwen Osayi (Journal of Social Science and Humanities, 2026)
One of the problems of contemporary human society is the problem of class struggle and the inherent contradictions that are inherent in socio-economic and political society. Marx attempts to address the contemporary issues of class struggle. There are certain concepts that are closely associated with Marx’s political economy such as class struggle, alienation, historical materialism, dialectical materialism, and political economy. Marx’s conception of political economy cuts across his ideological reconstruction and theoretical templates of politics, religion, law, literature, the state, ideology, and culture. The objective of this paper is to reveal that Marx’s conceptualization of society reveals the theory of class struggle, theory of revolution, theory of political economy and the theory of history. This paper is robust, timely and imperative because it reveals the interconnectedness between political reality and economic reality. Marx’s conception of political economy reveals the critical importance of human liberation and emancipation from the shackles of poverty and alienation. Marx could be referred to as a social emancipator because he vehemently believes in the socio-economic and the political freedom of the individuals in society. This paper adopts the method of analysis and hermeneutical methodology in discussing the interconnectedness between political reality and economic reality in Marx’s theoretical reconstruction. Findings, however, revealed that Marx’s conception of political economy is a practical demonstration of human condition and socio-economic and political existence. This paper, however, concludes that Marx’s conception of society with regards to his theoretical reconstruction on political economy aims at addressing the fundamental problems of humanity.